Structures of Marburgvirus glycoprotein and its complex with NPC1 receptor - Gang Ye; Fan Bu; Hailey Turner-Hubbard; Morgan Herbst; Lanying Du; Ge Yang; Bin Liu; Fang Li (Nature, 2026)
Abstract Marburgviruses (MBVs) cause severe haemorrhagic fever with higher fatality rates than Ebola virus (EBOV) 1–4 . Here we show that the MBV glycoprotein (GP) mediates viral entry more efficiently than EBOV GP. Using cryo-EM, we determined structures of MBV GP in three states: (1) unbound; (2) bound to its endosomal receptor NPC1; and (3) complexed with a neutralizing nanobody. The glycan cap shields the receptor-binding site from NPC1 but only partially from the nanobody, enabling limited immune evasion. After glycan cap cleavage, NPC1 binds to MBV GP in a distinct orientation compared with EBOV GP, providing an additional anchor and enhancing receptor affinity. NPC1 engagement also induces substantial conformational changes in MBV GP, probably facilitating membrane fusion. Furthermore, MBV GP is susceptible to the neutralizing nanobody, which mimics NPC1 at the receptor-binding site. Together, our findings reveal MBV GP as a highly efficient entry mediator and suggest structural mechanisms that may contribute to its enhanced entry efficiency.